Spannungsvolle Kooperation: Überlegungen zur Komplementarität und Differenz von Dramatischer und Kommunikativer Theologie aus der Sicht eines dramatischen Theologen - Wandinger, Nikolaus (Zeitschrift für katholische Theologie, 2010)
Dramatic Theology and Communicative Theology have been cooperating for over a decade in the research center Religion – Violence – Communication – World Order. The article reflects on the particularity of the two theological approaches and sees them as partly being grounded in the respective ways of origin (one in the context of teaching and learning, the other in searching for a consistent systematic view-point). Each approach incorporates its own «non-theological" method: theme-centered interaction and mimetic theory. Their role is described briefly and the question addressed whether they pose a non-theological infringement on the two theological approaches. The article then argues that both approaches have a lot in common but are complementary through some of their different emphases. Finally the article states differences between the two and poses some critical questions to Communicative Theology from the point of view of Dramatic Theology.